Patient-Reported Outcomes and Surgical Quality - Hyland, Colby J.; Pusic, Andrea L.; Liu, Jason B. (Clinics in Colon and Rectal Surgery, 2023)
Delivering high-quality surgical care requires knowing how best to define and measure quality in surgery. Patient-reported outcomes (PROs) enable surgeons, health care systems, and payers to understand meaningful health outcomes from the patient's perspective and can be measured using patient-reported outcome measures (PROMs). As a result, there is much interest in using PROMs in routine surgical care, to guide quality improvement and to inform reimbursement pay structures. This chapter defines PROs and PROMs, differentiates PROMs from other quality measures such as patient-reported experience measures, describes PROMs in the context of routine clinical care, and provides an overview of interpreting PROM data. This chapter also describes how PROMs may be applied to quality improvement and value-based reimbursement in surgery.
Keywords: patient-reported outcomes; patient-reported outcome measures; quality of life; surgical quality